Surgical management of pulmonary arteriovenous fistula in a female patient - Ichiki, Yoshinobu (Int J Surg Case Rep, 2014)
INTRODUCTION: We herein describe a rare case of a pulmonary arteriovenous fistula (PAVF). PRESENTATION OF CASE: The patient was a 20-year-old asymptomatic female, admitted to our hospital because of an abnormal shadow in the right lung field on chest X-rays. Chest computed tomography (CT) revealed two nodules with well-defined margins in the right upper and lower lobes. Contrast-enhanced three-dimensional CT (3D-CT) revealed two enhanced solitary lung nodules which were connected with linear structures suggestive of feeding arteries and drainage veins, respectively. Based on these findings, we made a preoperative diagnosis of PAVF. We performed partial pulmonary resection of the right upper and lower lobes by video-assisted thoracoscopic surgery (VATS). The histopathological findings revealed small and medium-sized vascular channels composed of arteries with mild and irregularly thickened muscle walls and juxtaposed or seemingly anastomosing dilated veins. Based on these findings, a diagnosis of PAVF was confirmed. The patient had an uneventful postoperative course. DISCUSSION: A PAVF is often associated with various complications, and pregnancy could be a risk factor for these complications because of the increase in the shunt fraction. Females with known PAVF should be maximally treated prior to becoming pregnant as complications of PAVF during pregnancy can have devastating consequences. Therefore, we thought that treatment should be recommended in this case in the event she might later choose to become pregnant. CONCLUSION: Surgical resection using VATS for a limited number of ipsilateral isolated pulmonary arteriovenous fistulae is recommended due to its safety, low recurrence and low mortality rate.